Deriving The Upper Blow-up Rate Estimate for a Parabolic Problem - Rasheed, Maan A. (Iraqi Journal of Science, 2020)
In this paper, the blow-up solutions for a parabolic problem, defined in a bounded domain, are studied. Namely, we consider the upper blow-up rate estimate for heat equation with a nonlinear Neumann boundary condition defined on a ball in Rn.